Reachability of Fractional Dynamical Systems with Single Delay in Control using ψ-Hilfer Pseudo-Fractional Derivative - Selvam, A. Panneer; Govindaraj, V. (Journal of Applied Nonlinear Dynamics, 2026)
In this article, we study the reachability of linear and non-linear fractional dynamical systems with single delay in control in the sense of ψ-Hilfer pseudo-fractional derivative. The necessary and sufficient conditions for reachability of linear fractional dynamical systems are obtained using Grammian matrix which is expressed by the Mittag-Leffler functions (one or two parameters). Sufficient conditions for reachability of nonlinear fractional dynamical systems are obtained by using Schauder’s fixed point theorem. Two numerical examples are offered to help better understand of theoretical results.